«I knight you». Ceremonies of entry into the Order of Chivalry in the Archive of the Royal Chancellery of Granada. Documentary corpus - Fernández Valdivieso, José Luis (Cuadernos de Historia del Derecho, 2021)
The present objective is to edition forty-one investitures of armed knights, officiated between 1365 and 1511 and kept in the Archive of the Royal Chancery of Granada. This collection is accompanied by a brief introductory study on the procedures followed in the Royal Court and Chancery that explain the profusion of this documentation in the Granada archives.
Keywords: Crown of Castile; Chivalry; Archive of the Royal Chancery of Granada; Lawsuit of nobility